Inclusive Governance at Local Level: A Case Study of Local Policymaking Process in Kirtipur Municipality - Bhattarai, Krishna Prasad; Pokharel , Binod (Tribhuvan University Journal, 2022)
Inclusive policies lead local governments to function in public service effectively. This study explored the process and inclusive practices during the formulation of policies at a local level. Taking the case of Kirtipur Municipality, one of the local governments in Kathmandu valley, the primary tools, and techniques for data collection were the Key Informant Interview (KII) with municipal executive members, Focused Group Discussions (FGD) with women network members, and Dalit network members, and reviews of policies formulated by the municipality. The finding has shown that inclusive policymaking is imperative in local government, which demonstrate uncovers a system of governance and creates inopportunity to deliver public services inclusively to people in general and priority groups. It concludes that a specific group of people developed local policies with legitimate authority but without comprehensive consultations and engagement with women and disadvantaged people. The participation and representation of women and Dalits in the policy-making process have been ignored and as a result, local policies failed to grasp the inclusive perspective due to the dominance of the patriarchal mindset among policymakers and weak policy-influencing capacities of women, Dalits, and disadvantaged communities. The failure further resulted in continued subordination of women, Dalit, and disadvantaged people, reinforcing existing patterns of exclusion and disengagement.